339 PATIENTS' PERCEPTION OF CULTURAL COMPETENCE AND OUTCOMES IN HEALTH-RELATED QUALITY OF LIFE. (1st January 2005) - Bussey-Jones, J. C.; Diaz, Y.; Shaw, A.
Abstract : Background: An increasingly diverse population and ongoing health disparities have focused national attention on the cultural competence of health care providers and the role of training on cross-cultural issues in medical school. Despite this emphasis, few data exist on the association of cultural competence with clincally relevant outcomes. The purpose of this study is to determine the relationship between patients' perception of physician's cultural competence and quality of life measures. Methods: The CCTOP study (Cultural Competency Training and Outcomes in Patients) is a multicenter, cross-sectional study of patients and their physicians' attitudes regarding culture, bias, and clinical care. To date, a 76-item questionnaire has been administered to 184 patients presenting for care at three geographically diverse university clinics. Patients were asked to agree or disagree on a 4-point Likert scale with the statement "My doctor is aware of my cultural beliefs." Our main outcome was health-related quality of life. We examined the association between several subscales of the SF36 Health Survey and patient perception of their physician's cultural awareness. Linear regression analyses were performed controlling for age, gender, race, education and income. Results: We report preliminary results on the first 184 patients surveyed. The patients' mean age was 56 years. Seventy-one percent of respondents were female. Forty-five percent of these patients identified themselves as African American, while 23% were Hispanic, and 29% white. Bivariate analysis revealed that higher ratings on physical functioning were associated with patients' perception that their physician was aware of their cultural beliefs, 55.3 vs. 46.7 when patients perceived their physician to be unaware (p = .04). In addition, the mean bodily pain scale yielded similar results 52.9 bodily pain score when patients considered their physician to be culturally aware compared to 41.1 for the "unaware" group (p = .02). The relationship between bodily pain and physician cultural awareness persisted in the regression models. Conclusion: We found that patient perception of physician cultural awareness was associated with improved quality of life as measured by the physical functioning and bodily pain subscales. These study results begin to build the case for clinical relevance of cultural awareness and competence.